Scientific exegesis of al-quran and its relevance in dealing with contemporary issues: An appraisal on the book of ‘al-jawahir fi tafsir al-quran al-karim - Lukman Abdul Mutalib; Abd Hamid Abd Murad; Ismail W.A.F.W.; Baharuddin A.S.; Mohamed M.F.; Wafa K.A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by Scopus